Regime equations for mountain streams in the Cauca Region of Colombia - Arbeláez, Ana C., author; Guevara, María Elvira, author; Posada, Lillian, author; González, Luís Jorge, author; Gallardo, Carlos A., author; Colorado State University, publisher (Colorado State University. Libraries, 2007)
Knowledge of the dimensions of a stable stream channel during a specific period of time and of its corresponding forming discharge allows determining parameters of regime equations for a region, which enhance the design of channels in other zones with similar characteristics. Nowadays, the state-of-the-art for regime channel does not include the typical streams of the Department of Cauca characterized by relative steep slopes, high annual precipitation in the order of 2500 – 3000 mm, high discharge and varied geology. In this article, we present regime type expressions obtained from a research done in mountain streams of the Department of Cauca, Colombia.
Hydrology days 2007
AGU hydrology days 2007
2007 annual AGU hydrology days was held at Colorado State University on March 19 - March 21, 2007.